Taking the frozen elephant trunk technique to the next level by a stented side branch for a left subclavian artery connection: a feasibility study. (22nd January 2021) - Grabenwöger, Martin; Mach, Markus; Mächler, Heinrich; Arnold, Zsuzsanna; Pisarik, Harald; Folkmann, Sandra; Harrer, Marie-Luise; Geisler, Daniela; Moidl, Reinhard; Winkler, Bernhard; Bonatti, Johannes; Czerny, Martin; et al.
Abstract: : OBJECTIVES: Our goal was to develop a modified frozen elephant trunk (FET) prosthesis with a stented left subclavian artery (LSA) side branch for LSA connection and to perform preclinical testing in a human cadaver model. METHODS: We measured aortic diameters, distance between and diameters of supra-aortic vessels and the distance from the LSA offspring to the level of the left vertebral artery offspring in 70 patients. Based on these measurements, a novel FET prosthesis was developed (Cryolife/Jotec, Hechingen, Germany) featuring a stented side branch for an intrathoracic LSA connection. The feasibility and ease of implantation were tested in 2 human cadaver models at the Anatomical Institute of the Medical University Graz. A covered stent graft (Advanta V12™ by Atrium Medical Corp., Hudson, NH, USA) was used for an LSA extension. RESULTS: Accurate deployment of the novel FET prosthesis with anatomical orientation of the stented side branch towards the LSA ostium followed by consecutive stent graft deployment was feasible in both cases. Proximalizing the distal anastomosis level from zone 3 to zone 1 not only diminished the complexity of the procedure but substantially facilitated the completion of the distal anastomosis. A 2.5-cm long extension stent graft was sufficient to seal to the LSA and to maintain left vertebral artery patency in both cases. CONCLUSIONS: This initial study in human anatomical bodies could demonstrate the feasibility of implanting a newly designed FET prosthesis. This evolution of the FET technique has the potential to substantially ease total aortic arch replacement by proximalization of the distal anastomosis into zone 1 and by shortening spinal and lower body hypothermic circulatory arrest times via a stented side branch to the LSA. This direct connection enables early restoration of systemic perfusion.